Civic Education in Border: Forms of Strengthening Nationalism for Indonesian-Malaysian Border Communities in Sebatik Island - Wahyudi Wahyudi; Roro Nanik Setyowati; Rianda Usmi; Mi'rojul Huda (PAEDAGOGIA, 2024)
The existence of Citizenship Education in Indonesia has a significant and strategic role in the effort to build the character of the nation. Citizens with the Spirit of Nationalism are one form of the nation's character. Citizenship education is taught from elementary school to college by the School of Citizenship Education (SCE). Citizenship Education in the Community is called the Community of Citizenship Education (CCE). The existence of Citizenship Education in strengthening the nationalism of citizens is also present in the border area, precisely in Sebatik Island Nunukan Regency, North Kalimantan Province, which is directly adjacent to Malaysia. However, people in this region use ringgit money to buy, sell, and use Malaysian products to meet their daily needs, as well as the alleged existence of dual citizenship that is legally prohibited in Indonesia, which shows indications of weakening nationalism. This research uses a Qualitative Approach with the Case study method with the Informant who took a purposive sampling of Government, Community Leaders, Youth Leaders, Teachers, Military, and Journalists. This research aims to find forms of Citizenship Education for people in border areas of the State to Strengthen Nationalism. The results show that Forms of Strengthening border community nationalism are implemented through Community Citizenship Education by the Government, Entrepreneurs, Youth, and Media. Meanwhile, the School of Citizenship Education is implemented by Citizenship Education Teachers.